The Two-Pillar Churches of Pereyaslavl-of-Russia: Byzantine Context - Yolshin, Denis D. (Actual Problems of Theory and History of Art, 2013)
The new variants of the hypothetical reconstruction and typological definition of the three Old Russian churches are proposed, notably the St. Andrew church, the Dormition church and the Saviour burial church in Pereyaslavl’ the Southern (constructed in the late 11th and early 12th centuries). The previous reconstruction suggested by Aseyev, Kharlamov and Trofimenko, based on the principle of the alternately resting arches, are challenged since they have no analogs in the Mid-Byzantine building practice. Considering the monuments in the Byzantine context, the author suggests to regard the St.Andrew church to be of the single-domed octagonal type, and the Saviour church and the Dormition church, to the inscribed cross type, possibly with columns as western dome butresses.
Keywords: Pereyaslavl’ the Southern; Pereyaslavl’-Khmelnitsky; Old Russian architecture; premongolian period; Byzantine architecture